Kazanie krótkie o Męce Pańskiej Piotra Skargi — przekład oracji Stefana Tucciego wygłoszonej przed papieżem Grzegorzem XIII - Kuran, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
This paper concerns strategies which were applied by Skarga when he was translating the Good Friday oration of Italian Jesuit Stefano Tuccio (delivered before Pope Gregory XIII in 1583). The strategies were divided into four groups (according to translatological and rhetorical key): adiectio, detractio, transmutatio i immutatio. The very brief sermon demanded special tools. Skarga performed an unusual task. He retained spirit of the original and at the same time demonstrated an invention. The preacher had to choose between two strategies of translation – the method of words and the method of a sentence (or a sense). He unambiguously decided for the second one. His fundamental unit of translation was a sentence (its sense, a rhetorical figure, a sound), not a word. Skarga was the translator but primarily he felt he was the rhetor and this (his rhetorical preparation and skill) determined the character of the translation.